ANALISI KESULITAN DALAM PEMBELAJARAN AL-QURAN HADITS DITINJAU DARI ASPEK KOGNITIF SISWA SMO SWASTA AD-DAKWAH SEI RAMPAH - Siti Iza Mutia; Khairuddin Lubis; Yurmaini Yurmaini (HIBRUL ULAMA, 2025)
This research is motivated by the attention of the author who has made initial pbservations at the SMPS Ad-Dakwah Sei Rampah about difficulties in learning the Al-Qur’an Hadith in terms of cognitive aspects of class VII students, where a child must have difficulties in the learning process, especially children who have cognitive abilities below average, which makes it difficult for them to learn.The purpose of the research in this thesis is to find out the learning difficulties experienced by students in the Al-Qur'an Hadith subject in terms of the cognitive aspects of students at Ad-Dakwah Sei Rampah Private Middle School and to find out the supporting and inhibiting factors in overcoming learning difficulties Al- Qur'an Hadith from the cognitive aspect of Ad-Dakwah Sei Rampah Private Middle School students. This type of research is field research using qualitative methods. Data collection uses interview, observation and documentation The results of this research show that students' difficulties in learning the Al-Qur'an Hadith are that students have difficulty understanding the connected letters of the Al-Qur'an, students have difficulty in pronouncing the makhrijul letters, practicing the rules of reciting tajwid and memorizing the Al-Qur'an. and Hadith smoothly. Apart from that, the supporting factors in overcoming difficulties in learning Al-Qur'an Hadith are the existence of Al-Qur'an guidance and also complete and adequate infrastructure. Then, the inhibiting factors are the low interest and motivation of students and also family factors.